EFEKTIVITAS MEDIA PEMBELAJARAN DARING TERHADAP KELANCARAN PENGAJARAN GURU SEKOLAH MINGGU UNTUK USIA 9-12 TAHUN DI GEREJA BETHEL INDONESIA TABGHA BATAM CENTRE - Pranada Pane; Aries Sukmawati; Triades Sidabutar (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2023)
During the Covid-19 pandemic, many things happened, even an activity was hampered and even if it continued, of course, it was done with good calculations. Christian worship is no exception, which usually worships at church, but during the Covid-19 pandemic, many churches were carrying out their services. through online worship and in this case including the Sunday school children's worship where Sunday school activities are also transferred online (in the network). Thus Sunday school teachers provide their teaching online as well. But deep. Using online learning media has its own challenges, including the existence of Sunday school teachers who do not master the media, causing children to be less focused during worship so that learning becomes less effective